Meningkatkan sistem penjualan dan akuntansi dengan enterprise resource planning - Sherlyntan Mutiara Faiza (Department of Accounting Universitas PGRI Yogyakarta, 2024)
This research aims to address sales and accounting issues in the warehouse management system at PT Bedikari and to analyze, design, and implement an Odoo enterprise resource planning (ERP) system using the sales and accounting modules. This study uses a qualitative method. This research begins with a preliminary phase that identifies problems, proposes business processes, defines system requirements, and implements the system. The problem with PT Berdikari is that sales management and accounting remain manual. The implementation of Odoo enterprise resource planning (ERP) addressed sales and accounting business process problems at PT Berdikari. This research concludes that implementing the Odoo enterprise resource planning (ERP) System at PT Berdikari can integrate the sales and accounting modules; sales transaction data entered in the sales module is automatically synchronized with the accounting module. Every recorded sales transaction automatically affects the accounting records, including the recognition of receivables and revenue. This can facilitate the rapid and accurate acquisition of sales and accounting information.